Gas Prices, Traffic, and Freeway Speeds in Los Angeles - Burger, Nicholas E; Kaffine, Daniel T (The Review of Economics and Statistics, 2009)
Using detailed data on traffic speeds for 12 Los Angeles freeway routes from 2001 to 2006, we investigate aggregate behavioral response to gasoline prices. If traffic is free flowing, drivers should slow to more fuel-efficient speeds as the price of gasoline rises. However, we find little evidence that drivers respond to increased fuel costs by slowing down. When congestion constrains traffic flow, freeway speeds should rise with gasoline price, and we find a $1.00 increase in price raises average freeway speeds by approximately 7% during rush-hour periods. Finally, we introduce a novel method to calculate the short-run vehicle miles traveled demand elasticity during rush hour.